Mandibular third molar odontectomy and drug of choice: a case report - Tanumiharja, Leonardo Jaya Setiadi; Purnomo, Yohanes Yoppy; Pradana, Tio; Suwindere, Winny; Tanumiharja, Marvin Jaya Setiadi; Caroline, Sharon Angelica (Science Midwifery, 2026)
Impacted tooth is an abnormal tooth eruption, usually caused by adjacent tooth near it or pathologic tissue. Impacted tooth is partially erupted or cannot be erupted entirely because it is blocked by bone or surrounding soft tissue or even both. The odontectomy procedure performed was the same as in other odontectomy cases. Initially, a flap was made to get a field of view, and division of the tooth structure was carried out in the lower third molar teeth into several parts. The results shown one week after the odontectomy procedure, no abnormalities were found and healing in the bones and soft tissue were seen after the procedure. From this case report, it can be concluded that in post-operative impacted tooth management, a minimum traumatic technique should be applied and the correct drug of choice and time of administration can give a high effective effect of managing patient's discomfort and high yield of infection prevention.